Line breaks in international rugby. - Diedrick, E.; van Rooyen, M. (World Congress of Performance Analysis of Sport VIII, 2008)
In conclusion approximately half of the line breaks resulted in a try being scored with an average of 2.2 tries being scored per match (range 0 - 6). However the potential to lose possession of the ball after a line break was very low, with only 0.8 line breaks per match resulting in lost possession. The backline players were more likely to create a line break (72%) than the forwards (28%). The line breakers were more likely to score the try than their support players.